2017
DOI: 10.1128/jvi.01148-17
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies Virus dUTPase UL50 Induces Lysosomal Degradation of Type I Interferon Receptor 1 and Antagonizes the Alpha Interferon Response

Abstract: Alphaherpesviruses that establish persistent infections rely partly on their ability to evade host antiviral responses, notably the type I interferon (IFN) response. However, the mechanisms employed by alphaherpesviruses to avoid this response are not well understood. Pseudorabies virus (PRV) is an economically important pathogen and a useful model system for studying alphaherpesvirus biology. To identify PRV proteins that antagonize type I IFN signaling, we performed a screen by using an IFN-stimulated respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 42 publications
0
60
0
Order By: Relevance
“…Recently, pseudorabies virus, a swine alphaherpesvirus, has been uncovered in which viral protein UL50 accelerates IFNAR1 degradation to avoid type I IFN responses. It also demonstrated that HSV-1 UL50 possesses similar activity, although the activity is milder (46). In fact, a previous study has already provided evidence that HSV-1 infection induces the degradation of IFNAR1 (13).…”
Section: Discussionmentioning
confidence: 74%
“…Recently, pseudorabies virus, a swine alphaherpesvirus, has been uncovered in which viral protein UL50 accelerates IFNAR1 degradation to avoid type I IFN responses. It also demonstrated that HSV-1 UL50 possesses similar activity, although the activity is milder (46). In fact, a previous study has already provided evidence that HSV-1 infection induces the degradation of IFNAR1 (13).…”
Section: Discussionmentioning
confidence: 74%
“…DAPI (4,6-diamidino-2-phenylindole) was purchased from Beyotime Institute of Biotechnology. The antibodies against PRV TK, PRV US3, PRV EP0 were described previously (30, 32, 33). Mouse polyclonal antibodies against PRV IE180, VP5 and gD were raised in mice individually with the 1-666aa, 710-1280aa, 240-400aa region of each protein as antigens.…”
Section: Methodsmentioning
confidence: 99%
“…This results in decreased IRF3 activation and subsequently lower levels of type I IFN production ( 132 ). Moreover, UL50 proteins from HSV-1 and PseudoRabies Virus (PRV) induce the lysosomal degradation of the Type I IFN receptor 1 ( 133 ). Although the mechanism is not yet deciphered, it also occurs in HCV infection ( 110 ).…”
Section: Viral Manipulation Of Autophagy-dependent Regulation Of Innamentioning
confidence: 99%